Detection of MAC address on remote computer - Shahrul Afzam, Mohamad (2010)
Computer is an important asset in development of technology nowadays.We can assume that each person and at least each home have a personal computer because it is a needed to a person.The missing of personal computer can give a big effect to someone even an organization.Due to that case, to overcome this problem,a system had created for searching the lost computer according to the place of the computer.This system named as "Detection of MAC Address on Remote Computer (DEMARC)" had developed.The web base and database system can operate faster in resolving the missing of computer. Detection of computer which applied in this system according the detection of MAC (Media Access Control) Address which it is locates at every computer.This particular identity can be detect after the moment the computer can access to the internet whether wireless or cable.